Efforts of the Islamic Study Groups in Overcoming Behavior Deviations in Adolescents' Life - Zihan Zahrotul Mukarromah (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2021)
This study uses a qualitative descriptive method that describes and explains what is in the field, with data collection techniques, participatory observation, in-depth interviews, documentation, and literature studies in Kembangkuning Village. The data analysis was carried out using qualitative data analysis. The study results showed that the Al-Hidayah Taklim Council was not sufficiently helpful in overcoming adolescent behavioral deviations. Because on the part of the Taklim Council it only conducts outreach to parents by making parents tell about their child's progress and the leader of the recitation at the Taklim Assembly gives advice and advice on religious knowledge that must be applied to their children during recitation at the Al-Hidayah Taklim Assembly, but this still can not cope with deviant behavior that occurs among adolescents. The efforts that the Taklim Assembly has made cannot help enough to overcome the problems in Kembangkuning Village. Therefore the researcher hopes that the Taklim Council (Islamic Study Groups) can contribute to helping to overcome deviant behavior with better efforts than what has been conveyed.